Massempe ’Traditional Bugis Game: Islamic Education and Law Perspective - Sarifa Suhra; A. Mustika Abidin (Lembaga Sembilan Tiga Community, 2020)
This study examines the traditional massempe' game 'in the perspective of education and Islamic law. Massempe 'game was originally a special game for the royal family (kings). Massempe 'was a game played by the ata (slaves) owned by the nobility in South Sulawesi. Now, massempe' has become a special game held for traditional ceremonies or to welcome guests of honor in South Sulawesi. Players who will compete in the arena consists of two adult men. Among those who will compete, there are two people who act as arbiters or referees called the pallape’. This massempe game is a physical sport that has core movements in the legs like kicking. This research uses a sociological and phenomenological approach. Performed in 2 different places, namely in the Village of Melle, District Dua Boccoe, and in the Village of Mattoanging, District of Tellusiattinge, Bone Regency. The data consists of primary and secondary. To collect the data, the author uses instruments in the form of observation guides, interview guidelines, and documentation tools. The results showed that this game is loaded with character values that support the application of Islamic educational values to the public such as; teya lara’ (never give up), malempu (honest / sportsmanship) and warrants (brave) even the value of unity, brotherhood also does not appear in it. Meanwhile, in the aspect of Islamic law, this game can be included in the category of violation of the law because it contains elements of violence. Still, until now, it has been preserved because it upholds the principle of benefits and customary law, namely the law